Comparison of the intraocular pressure following an intravitreal triamcinolone acetonide injection for diabetic macula oedema in vitrectomised and non-vitrectomised eyes. Issue 1 (8th January 2021) - Orii, Yusuke; Gozawa, Makoto; Takamura, Yoshihiro; Takeuchi, Yuko; Morioka, Masakazu; Yamada, Yutaka; Matsumura, Takehiro; Sugimoto, Masahiko; Inatani, Masaru
Abstract : Purpose: To compare the intraocular pressure (IOP) after an intravitreal triamcinolone acetonide (IVTA) between vitrectomised and non-vitrectomised eyes in patients with diabetes and diabetic macular oedema (DME). Design: Retrospective comparative study Methods: Medical records of 157 patients (157 eyes) with type 2 diabetes who received IVTA for DME were reviewed, and the best-corrected visual acuity, IOP and optical central retinal thickness (CRT) were compared preoperatively, at 1, 4, 12 and 24 weeks after IVTA between the vitrectomised and non-vitrectomised groups. Results: IOP significantly increased at 1 (p<0.0001), 4 (p<0.0001), 8 (p<0.0001), 12 (p=0.0019), 16 (p=0.0006) and 20 weeks (p=0.0191) in the non-vitrectomised group, whereas a significant increase was only observed at 1 (p=0.0003) and 4 weeks (p=0.0006) in the vitrectomised group. ΔIOP, IOP changes from baseline, in the non-vitrectomised group was significantly higher than that in the vitrectomised group at 4 (p=0.0014), 8 (p=0.0081), 12 (p=0.0032) and 16 weeks (p=0.0038). No significant difference was observed in logMAR and CRT at any time point after IVTA between the two groups. Conclusions: After an initial IVTA, increased IOP and ΔIOP from the baseline IOP were significantly more frequently observed in the non-vitrectomised than that in the vitrectomised group. IVTA is a safer and more effective treatment option for DME in vitrectomised than that in non-vitrectomised eyes.